Social Solidarity: Getting to Know the Uniqueness and Cultural Appeal of Traditional Dayak Tribes - Janes Sinaga; Indrayadi; Juita Lusiana Sinambela; Reviandari Widyatiningtyas (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is so that we as Indonesians can get to know, understand, and familiarize ourselves as a country that has a rich diversity of ethnicities and languages, so that we can adapt when one day we are on the island of Borneo and can be a means of strengthening the unitary state of the Republic of Indonesia. This study used a qualitative method by observing, and collecting data from the bibliography. So many tribes in Indonesia live side by side with their respective cultures and traditions. This makes Indonesia one of the largest multicultural countries in the world. Dayak is the name of a tribe in Indonesia among hundreds of tribal names in the archipelago. Because of the uniqueness that exists in the Dayak tribe, it is appropriate for tribes and foreign countries to be interested in knowing more deeply.